Clinical Examination of the Elbow - Dumontier, C.
WORKUP OF THE RHEUMATOID ELBOW CLINICAL WORKUP OF LATERAL EPICONDYLITIS (TENNIS ELBOW) CLINICAL WORKUP OF MEDIAL EPICONDYLITIS (GOLFER`S ELBOW) WORKUP OF ELBOW INSTABILITY (excluding radio-ulnar instability)